Narrative ethics - Newton, Adam Zachary (Harvard University Press, 1995)
The ethics of literature, formalists have insisted, resides in the moral quality of a character, a story, perhaps the relation between author and reader. But in the wake of deconstruction and various forms of criticism focusing on difference, the ethical question has been freshly engaged by literary studies, and to this approach Adam Newton brings a startling new thrust. His book makes a compelling case for understanding narrative as ethics. Assuming an intrinsic and necessary connection between the two, Newton explores the ethical consequences of telling stories and fictionalizing character, and the reciprocal claims binding teller, listener, witness, and reader in the process. He treats these relations as defining properties of prose fiction, of particular import in nineteenth- and twentieth-century texts.